Avaliação da qualidade de serviços públicos: o caso do Programa Academia da Saúde - Scherer, Nandria (2024)
Physical inactivity is a global problem, as it promotes the spread of non-communicable chronic diseases such as heart disease, respiratory issues, and mental health conditions like depression and anxiety. To address this, the Health Academy Program (PAS) was created through a government effort to combat population sedentarism and promote a healthy quality of life. Thus, the overall objective of this study was to evaluate the quality of services provided by the Health Academy Program (PAS) in Rio Grande do Sul, based on the perceptions of its users and the professionals involved. The adopted methodology consists of descriptive research characterized as a survey, with a mixed approach (quantitative and qualitative) based on the SERVPERF model, which comprises five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Data collection took place in seven municipalities in Rio Grande do Sul, covering a total of 355 users and 16 professionals. Quantitative data analysis was conducted with the aid of SPSS software, using techniques such as exploratory factor analysis and analysis of variance (ANOVA), while qualitative analysis followed Bardin's principles of content analysis. The results showed that, in general, users have a positive perception of the quality of services provided by PAS, particularly regarding empathy and the preparation of professionals. However, some criticisms were identified regarding the infrastructure of the centers where classes are offered. Factor analysis highlighted that service performance is the main determinant of perceived quality by users. Interviews conducted with professionals corroborated the findings of the quantitative research, indicating that the quality of service provided is directly influenced by the engagement of professionals and the available infrastructure. Additionally, a difference in perceptions was observed among users from different socioeconomic groups, age groups, and lengths of program participation, suggesting the need for targeted adjustments in certain regions. The main limitations of the research were its scope limited to one state, which restricts the generalizability of the results to other regions, and difficulties encountered in data collection, particularly in areas with low PAS adherence or geographic challenges. The study provides insights for improving the services provided by PAS, suggesting that managers focus on infrastructure improvements and schedule adjustments to better meet user demand.